Analysis of The Relevance of Fractional Material to The Creativity of Grade 3 Student in Elementary School - Feby Ayu Solikah; Sri Hartatik; Nafiah; Afib Rulyansah (Universitas Nahdatul Ulama Surabaya, 2022)
This research is motivated by the use of fractional materials in everyday life, as evidenced by the frequent application of fractional, materials in various fields, including architecture and science. The purpose of this study was to anlyze the relevance of fractions material to the creativity of grade elementary school students and to identify the creativity that can be generated by learning simple fractions material in grade 3 elementary school. The type of research used is a descriptive qualitative approach. This study uses data collection techniques used are data collection, data reduction, data presentation (display), verification and conclusions (conclusions drawing/verify). The validity test of the data used in this research is the data credibility test, dependability test, and confirmability test. The result showed (1) that there was a relevance of fractions material to the creativity of 3rd grade student, it could be seen from the material on problem solving related to fractional material in everyday life. (2) the skill obtaied by learning fractions material are that students can generate solutions, can generate ideas from solutions that are triggered, and can determine whether the action or solution that is triggered is a wise action or not and not only proposes a solution but can also realize it the solution.